2023
DOI: 10.20870/oeno-one.2023.57.2.7405
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: an innovative lever for grapevine breeding in times of climatic changes

Abstract: Climate change imposes numerous threats to viticulture. Different strategies have been developed to mitigate these effects that range from innovative vineyard management methods and precision viticulture to the breeding of new varieties and rootstocks better adapted to environmental challenges. Epigenetics refer to heritable changes in genome functioning that are not mediated by DNA sequence variations. The recent discovery that epigenetic memories can mediate acclimation and adaptation of plants to their envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As far as grapevine is concerned, genes encoding enzymes controlling histone methylation and/or acetylation are differentially regulated in response to abiotic stresses suggesting that epigenetic regulations are important in the response to stresses in this plant as well. The importance of DNA methylation in grapevine stress responses is also shown by changes in DNA methylation patterns induced after Flavescence dor ee infection (Pagliarani et al, 2020), or by the application of elicitors (Gao et al, 2020), and pieces of evidence are accumulating that it could play important roles in abiotic stress response and memory as well (reviewed in Berger et al, 2023). In Arabidopsis plants inoculated with microbes isolated from desert plants, histone methylation in the promoter regions of aquaporin genes was revealed to increase the tolerance to drought stress (Alwutayd et al, 2023).…”
Section: Prosit: a Complete Phenotyping Of Grapevine Plants Following...mentioning
confidence: 99%
“…As far as grapevine is concerned, genes encoding enzymes controlling histone methylation and/or acetylation are differentially regulated in response to abiotic stresses suggesting that epigenetic regulations are important in the response to stresses in this plant as well. The importance of DNA methylation in grapevine stress responses is also shown by changes in DNA methylation patterns induced after Flavescence dor ee infection (Pagliarani et al, 2020), or by the application of elicitors (Gao et al, 2020), and pieces of evidence are accumulating that it could play important roles in abiotic stress response and memory as well (reviewed in Berger et al, 2023). In Arabidopsis plants inoculated with microbes isolated from desert plants, histone methylation in the promoter regions of aquaporin genes was revealed to increase the tolerance to drought stress (Alwutayd et al, 2023).…”
Section: Prosit: a Complete Phenotyping Of Grapevine Plants Following...mentioning
confidence: 99%
“…It also has an essential role in maintaining DNA stability by suppressing the activity of transposable elements (TEs) and the transcription of potentially harmful exogenous genetic elements (e.g., viral DNA) [ 19 , 20 ]. DNA methylation primarily takes place when a methyl group (-CH3) is covalently attached to the fifth carbon of the pyrimidine ring of cytosine forming 5-methylcytosine (5-mC) or, more rarely, to the sixth carbon of the purine ring of adenine forming N6-methyladenine (N6-mA) [ 15 , 21 ].…”
Section: Overview Of Epigenetic Mechanisms In Plantsmentioning
confidence: 99%
“…Some recent epigenetic studies have further suggested a role of histone post-translational modifications in grape berries [ 23 ]. Specifically, more than 30 genes encoding polycomb repressive complex 2 (PRC2) components (chromatin regulatory complex), SET domain group (SDG) proteins (epigenetic modulators with methyltransferase activity), and HATs were identified to exhibit expression patterns that indicate a possible involvement of the respective proteins in berry development and ripening [ 15 , 68 ]. Transcription factors of the NAC and MADS-box families also appear to be involved in grape berry ripening process.…”
Section: Epigenetic Effects On Berry Development and Qualitymentioning
confidence: 99%
See 2 more Smart Citations